Single-cell transcriptome analysis for cancer and biology of the pancreas: A review on recent progress - Tamaddon, Mona; Azimzadeh, Mostafa; Gifani, Peyman; Tavangar, Seyed Mohammad (Frontiers in Genetics, 2023)
Single-cell sequencing has become one of the most used techniques across the wide field of biology. It has enabled researchers to look inside the whole transcriptome at the cellular level across tissues which unlocks many potentials for basic and applied studies in future diagnosis and therapy. Here, we review the impact of single-cell RNA sequencing, as the prominent single-cell technique, in pancreatic biology and cancer. We discuss the most recent findings about pancreatic physio- and pathophysiology thanks to this technological advancement in the past few years. Using single-cell RNA-sequencing, researchers have been able to discover cellular heterogeneity across healthy cell types as well as cancer tissues of the pancreas. We will discuss the new immunologic targets as well as new molecular mechanisms of progression in the micro-environment of pancreatic cancer studied using single-cell RNA-sequencing. The scope is not limited to cancer tissue, and we cover novel developmental, evolutionary, physiological and heterogenic insights that have also been achieved recently for pancreatic tissue. We cover all biological insights derived from single-cell RNA-sequencing data, discuss the corresponding pros and cons, and finally conclude how future research can move better by utilizing single-cell analysis for pancreatic biology.